Incidencia de los eventos El Niño y La Niña en el comportamiento de glaciares tropicales en perú - Medina y Colls., Gilberto (2019)
The events el niño and la niña in the tropical Pacific ocean occur periodically over time and have a clear incidence on growth and maintenance of the glacier surface of snow-capped mountains. The behaviour of the glacier surfaces of two snowy tropicals, the Pastoruri and the huandoy, located in the cordillera blanca of Perú were studied in the years when the events el niño and la niña occurred. This study was done applying a multifractal technique, the method of box counting, the normalized difference snow index nDsi and the relationship of bands of satellital images 3/5. multifractals modern techniques became very versatile, practical and sensitive in showing the impact of el niño and la niña in the multifractal spectral and for the estimation of glacier surface. The huandoy and Pastoruri decrease in average glacier surface was 10% in the last 22 years. The estimation of glacier surface for the conventional or multifractal methods was not significantly different in analysis such as related samples, which means that there is no distinction when using the siG or multifractals for determining the glacier area. The dimension D0 for the glacier surface was 1,8.